Daya Saing UMKM di ShopeeFood: Bagaimana Rating dan Review Mempengaruhi Keputusan Pembelian pada Restoran Non-Franchise - Rahayu Mardikaningsih; Moh. Riski (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
This literature study examines how ratings and reviews on the ShopeeFood platform influence consumer purchase decisions for non-franchise restaurants. As digital platforms become the primary gateway for culinary consumption, understanding the mechanism of electronic word of mouth is essential for small and medium enterprises. The analysis synthesizes concepts from consumer behavior theory, digital marketing literature, and electronic word of mouth studies. The findings reveal a two-stage decision process. First, star ratings function as an initial heuristic filter, shaping consumer perception and determining which restaurants enter the consideration set. Higher ratings with a substantial number of reviews increase the likelihood of being noticed. Second, verbal reviews mediate a more thorough evaluation process. Consumers seek detailed information about taste, portion size, delivery time, and packaging quality. They triangulate information by identifying consistent patterns across multiple reviews, prioritizing recent feedback, and assessing the balance between strengths and weaknesses mentioned. Photo attachments provide visual evidence that strengthens credibility. Emotional content in reviews psychologically influences readers, transmitting either enthusiasm or caution. Seller responses to reviews, particularly negative ones, signal the restaurant's commitment to customer satisfaction. This study provides a conceptual framework for understanding digital reputation management and offers practical implications for non-franchise restaurant owners navigating competitive platform ecosystems.